Pengetahuan Akuntansi Dan Kinerja UMKM Gerabah Kasongan Bantul - Erawati, Teguh; Damawati, Nur Alfina (Akuisisi : Jurnal Akuntansi, 2024)
Propose of this study wasito determine howiloan andiaccounting expertiseiaffected the performance of SMEs producing ceramics in Bantul. Pottery SMEs in Kasongan, Bantul, served as the research sample for this study, which employed hypothesis testing. Simple random sampling is the methodology employed in the sampling. The test findings demonstrate that accounting knowledge has a favorable impact on UMKM performance. Pottery Kasongan, or the idea that UMKM will perform better with sound accounting understanding. The second finding is that the availability of credit has a favorable impact on MSE performance, indicating that MSMEs will perform better if credit is more easily accessible. Theipurpose ofithis studyiis to offer resources forienhancing MSMEs'iperformance.